Tanggung Jawab Notaris Pengganti yang Melakukan Perbuatan Melawan Hukum dalam Pembuatan Akta Autentik - Mahadewi, I Gusti Agung Ika Laksmi; Purwanto, I Wayan Novy (Acta Comitas : Jurnal Hukum Kenotariatan, 2021)
Abstract The writing of this article aims to determine the authority of a substitute notary in carrying out the duties and positions of a notary and to find out the responsibilities of a substitute notary when committing an unlawful act in making an authentic deed. This research examines empty norms using normative research methods, with a statutory approach, a conceptual approach and an analytical approach. The search for legal materials uses document study techniques, as well as analysis studies using qualitative analysis. The results of this research show that the responsibilities of a Notary Substitute are the same as that of a Notary Public, although they have different competencies, which can be seen through the requirement that a substitute Notary be appointed only with a Bachelor of Law graduates and have worked in a Notary Office. This cannot guarantee that the Substitute Notary will work properly and will not discriminate against the position of the Notary who has responsibility for the deed he made without a time limit and is not associated with the responsibility of the Notary being replaced. The principle of responsibility based on error is the basis for imposing sanctions on a Substitute Notary who is proven to have committed an unlawful act and is responsible for his actions in Civil, Criminal, code of ethics as well as administratively and is not associated with the responsibility of the Notary being replaced. Abstrak Penulisan artikel ini bertujuan untuk mengetahui kewenangan notaris pengganti dalam menjalankan tugas serta jabatan notaris dan untuk mengetahui tanggung jawab Notaris Pengganti apabila melakukan perbuatan melawan hukum dalam pembuatan akta autentik. Riset ini mengkaji norma kosong menggunakan metode penelitian normatif , dengan pendekatan perundang-undangan, pendekatan konseptual dan pendekatan analisis. Penelusuran bahan hukum menggunakan teknik studi dokumen, serta analisis kajian menggunakan analisis kualitatif. Hasil riset ini menunjukkan bahwa tanggung jawab Notaris Pengganti sama dengan Pejabat Notaris meski memiliki kompetensi yang berbeda yang dapat dilihat melalui syarat diangkatnya notaris pengganti hanya dengan lulusan Sarjana Hukum dan pernah bekerja pada Kantor Notari s. Hal tersebut tidak dapat menjamin bahwa Notaris Pengganti akan bekerja dengan baik dan tidak mendiskriminasi jabatan Notaris yang memiliki tanggung jawab terhadap akta yang dibuatnya tanpa adanya Batasan waktu dan tidak dikaitkan dengan tanggungjawab Notaris yang digantikan. P rinsip pertanggungjawaban berdasarkan kesalahan merupakan dasar pengenaan sanksi kepada Notaris Pengganti yang terbukti melakukan perbuatan melawan hukum dan mempertanggungjawabkan perbuatannya secara Perdata, Pidana, kode etik serta pula secara administrasi dan tidak dikaitkan dengan tanggung jawab Notaris yang digantikan.